Equity swap: Empty voting - Pimentel, Dinarco Miguel Silva (2017)
The markets and financial instruments’ revolution, with complex products such as swaps, allowed investors who had an economic interest in a company to deplete their social interest, in what the doctrine calls empty voting and hidden Ownership. As it is well known, commercial companies, regardless of their nature and form, decide on matters that concerns them, by resolutions at a General Meeting. With the possibility of decoupling the voting rights from the economic interest, either by lending shares or by using equity swaps, it is possible that those who take advantage to these mechanisms and who, in principle, would have a direct interest in the regular and the normal development of a commercial company, i.e., the search for profit, position themselves as participants in the equity capital, protected and guaranteed, for their own benefit and outside the corporate interest. Thus, with this thesis, we will try to analyze this mechanism / phenomenon by interpreting the way of acting, consequences and ends reached, trying to integrate such behaviors as abusive deliberations, if they fulfill such framework. Based on an analysis of the validity of swap contracts in the Portuguese legal system, we will try to transpose them into their use in a corporate context. Therefore, Swaps and, in general, derivative instruments, representing the product of financial innovation, appear to, for the most inattentive, as an iceberg, where apparently only the visible part is known. However, swaps show a great potential for growth where the quantification, sometimes, is lacking, especially in the business context, where they have acquired a special relevance due to the needs of risks control that emerge from the markets or, as we will seek, allowing the pursuit of the personal and individual interests of those who participate in the equity capital of these companies using a specific type of equity swaps. Although in a synthetic way, due to the ease of contextualization and as a motto for the study that we will try to achieve, we can already affirm that this phenomenon, where equity swaps acquire significant importance and whose legality of the result is discussed, is based on the possibility of decoupling the right to vote that is inherent to the economic exposure related to the ownership of shares and, consequently, the prominence of the vote interest from the economic interest.